The Spiritual Bonds that constitute the Catolic Family in the (recent) Magisterium of the Catholic Church - Biały, Stanisław (Studia Teologiczne Białystok Drohiczyn Łomża, 2024)
The article is analyzed regarding the topicality of the accents of the Magisterium of the Catholic Church, current in the Catholic family and constituting the structure of its movement towards holiness. We can talk here about elements that have the scope of scaling its member into a deep community and that their character is spiritual (moral). emerging from them is the concept of the Catholic family as the „main Church”, comes from the enlightenment of its member, by putting God in the first place. The second is: the need to raise offspring in the Catholic spirit (socialization and instilling saving faith). Third, the auxiliary role of the Catholic Church (watching over teaching) and the state (watching over the definition of catechesis and respect for religious freedoms), without which meanings are defined, the educational process has not been identified as being at risk of failure. Spiritual limitations are the most important for the scale and durability of the family. The elements are a continuation of teaching in the spirit of teaching, but also constitute a framework for a completely new, i.e. more alternative and accessible existence. It was especially about the Final Report to Pope Francis entitled: The vocation of the family in the Church and in the world in the light of the 14th Synod of Bishops and the post-synodal exhortation Amoris laetita or the exhortation Evangelii gaudi. It seems that all documents of the Magisterium regarding the understanding of the Catholic family and its role in the modern world complement each other adequately. it is important when it appears, how it is recognized and responsible for accompanying spouses (parents) and resulting from their life of faith, and above all in a situation when they are in a great crisis (e.g. marital, family, moral, etc.).